Degradation of Tetracycline by Birnessite under Microwave Irradiation. (2nd September 2014) - Liu, Meng; Lv, Guocheng; Mei, Lefu; Wang, Xiaoyu; Xing, Xuebing; Liao, Libing
Abstract : The efficiency and factors affecting tetracycline (TC) degradation by birnessite under microwave irradiation (MI) were investigated under different initial TC concentrations, solution pH, MI time, and MI power. The crystal structure, degradation efficiency, and reaction mechanism were investigated using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and ultraviolet-visible spectroscopy (UV-Vis). The results showed that birnessite was an excellent microwave catalyst. The maximum TC removal efficiency by birnessite was 99% under MI at 400 W for 30 min in strongly acidic media. Under MI, the surface activity of birnessite increased, resulting in the ability to accelerate TC removal in high temperature.